Caracterização da alumina anódica porosa modificada por plasma - Silva, Karina Rodrigues da (2015)
In this study, the wettability of porous anodic alumina (PAA) surfaces modified by plasma was investigated. The porous anodic alumina films were grown on aluminum substrate using a two step anodization procedure in oxalic acid solution under potentiostatic regime. The surfaces of PAA films were modified by plasma treatment or plasma deposition techniques. Prior to surface modification, the impurities were removed by a plasma cleaning procedure. Oxygen was used in plasma treatment in order to produce hydrophilic surfaces. On the other hand, the plasma deposition (in HMDSO or HMDSO + argon mixture) was performed to produce hydrophobic surfaces or less hydrophilic surface. Electropolished aluminum without PAA film were used as reference. The influence of substrate morphology on wettability was analyzed. The morphological characterization was performed by scanning electron microscopy (SEM). The microstructural analysis was carried out using Fourier Transformed Infrared Spectroscopy (FTIR). A goniometer was used to measure the contact angle and evaluate the wettability of electroplished aluminum and PAA films. The results showed that the wettability of the samples was affect by chemical interactions of functional groups on the surface deposited after plasma treatment. The effect of the porous surface morphology on wettability was not significant compared to the plasma treated films with new chemical interactions effects.